Comparative Efficacy of Biologic Vs. Non-Biologic Therapies in Reactive Arthritis: a 52-Week Cohort Study - Ikhtiyor Turaev (Scientific Trends, 2024)
This study aims to compare the efficacy and safety of biologic versus non-biologic therapies in managing Reactive Arthritis (ReA) over 52 weeks. Methods: A cohort of 60 patients diagnosed with ReA was divided into two treatment groups, with 30 patients each receiving either biologic therapies (including TNF-α inhibitors) or non-biologic therapies (standard disease-modifying antirheumatic drugs). Patients were followed prospectively over 52 weeks, and clinical outcomes were assessed using standardized measures, including the Disease Activity Score (DAS28), remission rates, and adverse event profiles. Results: Patients in the biologic therapy group demonstrated significantly greater improvements in DAS28 scores compared to the non-biologic group (mean reduction: 2.8 vs. 1.9; p < 0.05). Remission rates were achieved in 70% of patients in the biologic group versus 50% in the non-biologic group. Adverse events were more frequent in the non-biologic group (40% vs. 25%), with gastrointestinal discomfort being the most common complaint. Both therapies were well-tolerated overall. Conclusion: Biologic therapies offer superior efficacy in reducing disease activity and achieving remission in Reactive Arthritis compared to non-biologic therapies, with a favorable safety profile. These findings support the consideration of biologic agents as a first-line treatment option for patients with moderate to severe ReA. Further studies are warranted to explore long-term outcomes and cost-effectiveness.
Keywords: Reactive arthritis (ReA), biologic therapy, non-biologic therapy, Tumor Necrosis Factor-alpha (TNF-α) inhibitors.